Involuntary Autobiographical Memories in Schizophrenia: Characteristics and Conditions of Elicitation - Allé, Mélissa C.; Berna, Fabrice; Danion, Jean-Marie; Berntsen, Dorthe (Frontiers in Psychiatry, 2020)
Involuntary autobiographical memories are mental representations of personally experienced past events that come to mind spontaneously, with no preceding attempt to recall them. They have been showed to be more frequent and more emotional in the psychosis continuum. Although schizophrenia is strongly associated with thought disorders, including cognitive intrusions of thought, images, semantic knowledge, research on patients' involuntary autobiographical memories is limited. We undertook two studies to compare involuntary and voluntary remembering in schizophrenia and the conditions in which involuntary memories occurs in those patients, both in daily life (n = 40), using a diary method, and in an experimental context (n = 50). Overall, results showed that the conditions of elicitation of involuntary memories differ in patients, as patients were more sensitive to memory triggers, especially internal triggers, in comparison to controls. Relatedly, patients' involuntary memories—mostly related to mundane events with low emotional load—were experienced more frequently. Although patients' involuntary and voluntary memories were less clear, more poorly contextualized and associated with a lower belief in occurrence than those of controls, patients considered them as more central to the self, in comparison to controls. The results are discussed in relation to patients' self-reflective impairments.